Project-Based Learning by using Science KIT to Enhance Confidence and Problem-Solving Skills in Fifth Grade Students (Universitas Negeri Semarang, 2019)
The purpose of this study is to test the effectiveness of PjBL model by using Science KIT to improve students' confidence and problem-solving skills. This research is done by using a quasi-experimental design with a type of non-equivalent control group design. The research subjects were 50 fifth grade students from Elementary School 02 Krompeng and Elementary School 01 Kalirejo. Data on students’ self-confidence and problem-solving skills assessment are collected through observation and tests. Using N-Gain analysis and t-test. Research results show that there are different results in terms of self-confidence attitudes between groups of students who follow PjBL model with Science KIT and the other groups of students who follow PjBL learning model, obtained a value (tvalue = 37.12 > ttable = 1.68), there are differences in learning outcomes as well, in terms of problem-solving skills between groups of students who follow PjBL learning model with Science KIT with groups of students who follow PjBL learning model, it is proven post-test result obtained in experimental class is 74.96 while in the control class is 60.72 (tvalue = 19.55 > ttable = 1.71). The results of this research are beneficial for teachers as an overview of condition self-confidence and problem-solving skills that can be taken into consideration in planning the lesson.